The topography of Taiwan Island mitigates the damage of tropical cyclone disasters in southeastern China - Jingwen Wu; Yinchi Zhang; Laiyin Zhu; Ruyuan Yang; Tonghua Su; Lan Wang; Lu Gao (Environmental Research Letters, 2025)
The intensity, structure, and path of tropical cyclones (TCs) are altered when they cross Taiwan Island, and this directly affects the severity of disasters in the southeastern coastal region of China, especially Fujian Province. Therefore, the extent of mitigating effect of Taiwan Island on Fujian Province-bound TCs requires investigation. Here, we classified 71 Fujian Province-bound TCs from 1984 to 2023 into two categories based on their track: Taiwan Island-crossing TCs (TCTs) and non-TCTs (nTCTs). We discovered that the duration of nTCTs was longer than TCTs, and nTCTs landing positions are more inclined to the southern Fujian Province with greater intensity as compared with TCTs. Due to the obstruction of Taiwan Island, the intensity of nTCTs with Fujian landfall was greater than that of TCTs cases. The disaster losses caused by nTCTs were significantly greater than those caused by TCTs. The number of victims, including deaths and missing people, as well as collapsed buildings, caused by nTCTs were three and two times greater than that caused by TCTs, respectively. Whether it is TCT or nTCT, the landing track and specific location determine the severity of the disaster. The damage caused by TCTs with southern tracks was more serious than that caused by TCTs with other tracks. The south -tracks caused more severe damage than north-tracks in the nTCTs category.